Design of a test bench for gas leaks using CFD simulation and IR-thermography detection - Fu, Xiaolong (Environmental technology, 2021)
A test bench was constructed to enable the study of the influence of different parameters for gas leaks using computational fluid dynamics (CFD) simulation and IR-thermography detection. The results show that the gas chamber should be larger than 300×300×300 mm3. The diameter of fan-sizing should be 100 mm2. However, the influence is not obvious when the temperature changes. Meanwhile, the influence of the geometry of flow disturbance objects is shown by a sphere and cubic type to be obvious. Based on the results of simulation and detection, a schematic diagram for gas leaks is designed. The parameters of the test bench are also confirmed. The simulated and designed test bench can be used to test gas leaks by IR-thermography in future research